Variability in group identity construction: A case study of the Australian and British Big Brother houses. (December 2017) - Sinkeviciute, Valeria
Highlights: This paper explores group identity construction in reality television discourse. The analysis focuses on linguistic devices and metapragmatic labels and comments. Australians engage in anti-group discourse, while the British stress in-group belongingness. There are differences between spontaneous and imposed group identity construction. In imposed groups, the original in-group identity is preserved and further promoted. Abstract: This paper explores how social identity is constructed and manifests itself in interaction in reality television discourse, two national versions of the gameshow Big Brother – Australia 2012 and UK 2012. The analysis concentrates on two forms of group formation, spontaneous and imposed, and how different attitudes towards group formation are revealed in interactional practices. The findings show that in both types of group formation, the prevailing tendency among the Australian housemates is the avoidance of public group discourse, especially when it might suggest the superiority/inferiority dichotomy. In the British house, on the other hand, groups are frequently referred to in terms of them being popular/unpopular, with the unpopular group striving to reach popularity. Furthermore, unlike in the case of spontaneous groups, unwillingly becoming a group member does not trigger group identity construction and explicit membership claims. In both houses, a strong link to the original group identity seems to be preserved.